Creación del manual de identidad visual corporativa de la marca Brilla - Huerta Camones, Susan Karol (2020)
The project was born from the need to design a corporate visual identity for the company Shines that allows its recognition and positioning in the sector market retail-boutique, focused on the sale of jewelry and casual-elegant clothing. Its differential benefit consists of only 5 pieces available per model, for women Peruvian women between 21 and 35 years of age from socioeconomic sectors A and B who are characterized for your safety and independence. For the creation process, theories were collected and analyzed of content layout necessary in the brand manual. It was investigated competition to determine the strengths and weaknesses of the sector. Then he took carry out the design process, such as the pieces on offline and online media, which are part of the Brilla corporate visual identity manual. Later, these were evaluated through target audience surveys and expert interviews to define the most characteristic and appropriate graphic option.